Educational Environment And Readiness For Self-Directed Learning At Two Nursing Institutions In Malaysia - Chit, Som Phong (2017)
Learning environment is an important factor for producing quality graduates and play an important role in the effectiveness of teaching and learning in nursing training institutions. In addition, self-directed learning is also an important factor that lead to the formation of life long learning culture as medical knowledge become more advance. The objective of this study is to compare two types of nursing institutions under Ministry of Higher Education and Ministry of Health Malaysia; one employing student centered learning approach, the other does not (yet) employing the approach, in terms of their educational environment and students’ self-directed learning readiness.